PECULIARITIES AND MODERN TRENDS IN THE ORGANIZATION OF HOTEL SERVICES - Yudina, O. I.; Nebaba, N. O.; Saihak, Ye. L.; Tatarenko, D. K. (Systems and Technologies, 2025)
The article examines the specific features and components of the service process organization in hotel establishments, as well as the current trends in its development that contribute to enhancing the quality and efficiency of hotel services. The objective of this article is to analyze and characterize the main elements involved in the organization of hotel service processes and to identify innovative directions for its development in the present-day context. The study investigates the stages of organizing the hotel service process and outlines their essential content. The factors influencing the quality of hotel services are identified and described, including staff training, hotel infrastructure and equipment, management efficiency, personalized customer service, implementation of new technologies, effective communication, partnerships, and feedback mechanisms. Based on the conducted analysis, the article highlights contemporary directions in organizing hotel service, such as the integration of new information and communication technologies (ICT), optimization via popular media platforms, the efficient role of a Social Media Marketing (SMM) manager, and the establishment of barter agreements. These contemporary approaches allow accommodation facilities to minimize advertising costs while significantly enhancing brand awareness and attracting new clientele. Using the experience and skills of an SMM manager ensures the successful implementation of a marketing strategy and a positive impact on the organization of the customer service process.The introduction of ICT innovations, characterized by the use of media platforms such as Facebook, Instagram, LinkedIn, and TikTok, the development and implementation of SMM manager responsibilities, and the formation of barter agreements with celebrities and influencers for promotional purposes represent current trends in hotel service organization that impact the growth of service quality and operational performance of hotel enterprises. The factors that influence the quality of service to consumers of hotel services have been identified, as well as modern directions for organizing the service process and approaches to improving its efficiency and quality have been established. They can be used in further research for planning activities on a progressive basis and for developing strategies for hotel establishments.